2014
DOI: 10.1007/s11626-014-9782-x
|View full text |Cite
|
Sign up to set email alerts
|

Cell kinetics, DNA integrity, differentiation, and lipid fingerprinting analysis of rabbit adipose-derived stem cells

Abstract: Human adipose tissue has been described as a potential alternative reservoir for stem cells. Although studies have been performed in rabbits using autologous adipose-derived stem cells (ADSC), these cells have not been well characterized. The primary objectives of this study were to demonstrate the presence of adipose-derived stem cells isolated from rabbit inguinal fat pads and to characterize them through osteogenic and adipogenic in vitro differentiation and lipid fingerprinting analysis. The secondary obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
2
12
0
5
Order By: Relevance
“…More than three passage ADSCs were prepared for the subsequent experiment. Previous reports have confirmed the presence of stemness in ADSCs extracted by this method [6,20].…”
Section: Isolation Of Adscssupporting
confidence: 68%
See 1 more Smart Citation
“…More than three passage ADSCs were prepared for the subsequent experiment. Previous reports have confirmed the presence of stemness in ADSCs extracted by this method [6,20].…”
Section: Isolation Of Adscssupporting
confidence: 68%
“…However, the entire grafting process remains relatively complicated, time-consuming, and requires special materials. In our study, a simple and inexpensive Vc-mediated procedure was used to obtain ADSC sheets [20].…”
Section: Discussionmentioning
confidence: 99%
“…More than three passage ADSCs were prepared for the subsequent experiment. Previous reports have con rmed the presence of stemness in ADSCs extracted by this method [6,20].…”
Section: Isolation Of Adscsmentioning
confidence: 59%
“…Additionally, they revealed that the sheets contained collagen I and III, bronectin, and vitronectin, and exhibited stable adhesion to the surface of cartilage matrix. We investigated the optimal condition of Vc-induced ADSC sheets formation and indicated osteogenic potential of the sheets 20 . However, the properties of Vc-induced cell sheets have many unclear parts such as strength, species, incubation period, and quantity of Vc.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbits have a large amount of adipose tissue and a used in basic science for different purposes for many years. Regarding tissue engineering approaches, rabbit animal models have been used for urethral, cartilage, and vocal fold reconstruction (Barretto et al 2014). This paper focuses on the characterization of expression profiles of clusters of differentiation (CDs) in rabbit ADSCs used as immunosuppressive agent in rabbits undergoing urinary bladder allografts.…”
Section: Introductionmentioning
confidence: 99%